Ajaran Paulus tentang Kedatangan Yesus, antara Janji Keselamatan dan Panggilan untuk Hidup Kudus (International Forum of Researchers and Lecturers, 2025)
Paul's educating on the moment coming of Jesus Christ plays a imperative part in forming Christian religious philosophy and morals. In his epistles, Paul emphasizes that the return of Christ isn't simply a promise for long haul; it may be a living reality of confidence that provides trust and changes the way devotees live. The call to heavenly living within the present is integrated with the guarantee of salvation that will be satisfied at Christ's return. Agreeing to Paul, confidence in Christ must be illustrated through a life filled with love, truth, and sacredness. This is often since the hope of the Lord's coming is an fundamental portion of the moral obligation of each devotee. The understanding of Christ's return, in Paul's point of view, isn't only eschatological but too profoundly associated to the practical viewpoints of the believer's way of life. Within the setting of the early church—marked by abuse, doctrinal disarray, and ethical crisis—Paul demands that the trust of Christ's return ought to result in a life that's satisfying and commendable some time recently God. The long run. coming of Christ includes not as it were judgment or eminence, but too every day reliability. The point of this ponder is to investigate how Paul gets it the moment coming of Jesus in connection to the guarantee of salvation and from the values of the Kingdom of God.